Rectal corticosteroids versus alternative treatments in ulcerative colitis: a meta-analysis. Issue 6 (June 1997) - Marshall, J K; Irvine, E J
Abstract : BACKGROUND: Clear strategies to optimise the use of corticosteroids in ulcerative colitis are lacking. AIM: A meta-analysis was undertaken to examine critically the role of rectal corticosteroids in the management of active distal ulcerative colitis. METHODS: All reported randomised controlled trials were retrieved by searching the Medline and EMBASE databases and the bibliographies of relevant studies. Trials which met inclusion criteria were assessed for scientific rigour. Data were extracted by two independent observers according to predetermined criteria. RESULTS: Of 83 trials retrieved, 33 met inclusion criteria. Pooled odds ratios (POR) showed conventional rectal corticosteroids and rectal budesonide to be clearly superior to placebo. In seven trials, rectal 5-aminosalicylic acid (5-ASA) was significantly better than conventional rectal corticosteroids for inducing remission of symptoms, endoscopy, and histology with POR of 2.42 (95% confidence interval (CI) 1.72-3.41), 1.89 (95% CI 1.29-2.76), and 2.03 (95% CI 1.28-3.20), respectively. Rectal budesonide was of comparable efficacy to conventional corticosteroids but produced less endogenous cortisol suppression. Side effects, although inconsistently reported, were generally minor. A cost comparison of rectal preparations showed 5-ASA to be less expensive than corticosteroids. CONCLUSIONS: Rectal 5-ASA is superior to rectal corticosteroids in the management of distal ulcerative colitis.